2022
DOI: 10.3390/f13050763
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Hormones and Biochemical Changes during Flower Development and Florescence in the Buds and Leaves of Lycium ruthenicum Murr

Abstract: Lycium ruthenicum Murr. is one of the most important shrubs grown in northwest China. Healthy buds and leaves of L. ruthenicum Murr. were selected for the present study. Flower development was divided into six stages, namely, flower bud pre-differentiation (I), late flower differentiation (II), squaring stage (III), dew crown period (IV), open stage (V) and senescent stage (VI). Endogenous hormone content and specific value, soluble sugar, sucrose, starch, and soluble protein were measured, and ABA/IAA, ABA/GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…ZR is involved in flower organ morphogenesis and promotes cell division and growth. In Lycium barbarum , high levels of ZR promoted flower bud differentiation [ 31 ]. In apples, high levels of ABA and IAA favored the induction of flower formation and floral organ primordial differentiation [ 32 ], but high levels of GA3 were detrimental to floral bud differentiation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZR is involved in flower organ morphogenesis and promotes cell division and growth. In Lycium barbarum , high levels of ZR promoted flower bud differentiation [ 31 ]. In apples, high levels of ABA and IAA favored the induction of flower formation and floral organ primordial differentiation [ 32 ], but high levels of GA3 were detrimental to floral bud differentiation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also shown that endogenous hormone content and their balance plays an essential role in the aging process of perennials ( Munné-Bosch & Lalueza, 2007 ; Guo et al, 2022 ). Ethylene and abscisic acid (ABA) are recognized as key hormones in plant aging, and these play critical role in the regulation of growth and development of the entire life cycle of plants ( Zwack & Rashotte, 2015 ; Niu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous hormones regulate flower bud differentiation by influencing plant intrinsic physiological and biochemical processes [17][18][19][20]. The IAA content in leaves and buds increased during late flower bud differentiation in Lycium [21]. Cytokinin (CTK) can increase the number of flower buds by promoting the expression level of flowering genes, such as FT and SOC1 [22,23].…”
Section: Introductionmentioning
confidence: 99%